Reliability and durability of polymer insulators of the contact network - A. M. Luk’Yanov; Yu. G. Chepelev; A. A. Luk’Yanova (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
On the network of electriﬁed railroads and power lines of advanced countries there is an intensive work undergoing on the conversion of traditional insulating structures made of porcelain and glass to new ones - polymeric. In order to minimize mechanical damage, it is necessary ﬁrst of all to investigate the stress-strain state in the connection zone “end terminal - ﬁberglass rod”, and on the basis of the results obtained, to develop a number of design solutions that make it possible to provide the required reliability of such connection. The analysis of the stress-strain state and the strength of the joint between the ﬁberglass rod and the end terminal is of greatest interest, taking into account the viscoelastic properties of the glue (glue creeping). Authors present a method for calculating axis-symmetric glue joints of polymer insulators based on the ﬁnite element method. The stress state of the junction zone (“end terminal - ﬁberglass rod”) is analyzed. Optimum sizes of the glue-joint connection of the insulator are determined taking into account the viscoelastic properties of the glue. The results of testing the models of polymer insulators of the contact network in the temperature range -60 ... + 100 °C are given and the life of tension (suspension), ﬁxation and console polymer insulators is estimated on the basis of the principle of temperature-time analogy. The proposed technique for assessing the stress-strain state of the glued joint of polymer insulators, taking into account the viscoelastic properties of the adhesive, allows to determine the optimal parameters of the end caps, taking into account the time of action of the load on the insulator. An analysis of the experimental curves of durability has made it possible to establish the norms governing the change in the durability of a polymer insulator, depending on the load acting on it. A load, that provides reliable operation of the polymer insulator for 30 years, can be accepted for tension insulators, which is not more than 40 % of the destructive insulator, and for ﬁxative and console - not more than 45 and 50 % respectively.